Spectral narrowing and locking of a vertical external-cavity surface-emitting laser using an intracavity volume Bragg grating - Giet, S. (2009)
We report the use of a volume Bragg grating as an output coupler mirror to improve and stabilize the spectral characteristics of 1058-nm vertical-external-cavity surface-emitting laser which is thermally managed using an intracavity diamond heatspreader. Spectrally narrow and locked emission with up to 645 mW of TEM0 ; 0 output power is demonstrated.